Bulk and single‐nucleus analysis of the 3xTgAD cortex and hippocampus transcriptome. (December 2021) - Rezaie, Narges; Gutierrez, Gabriela Balderrama; Liang, Heidi Yahan; Forner, Stefania; Mortazavi, Ali; ,
Abstract: Background: Clinical trials for potential Alzheimer disease (AD) drugs have a high failure rate due to the fact that most drugs are successful in mouse models but are not translatable to humans. Mouse models fail to fully recapitulate the pathology, specially presenting plaques and tangles at the same time. The 3xTgAD mouse model contains three mutations associated with familial AD (APP Swedish, MAPT P301L, and PSEN1 M146V), and it presents both plaques and tangles accumulation at later stages of development. Cognitive impairments happen by 4 months, but there is no data that indicates neuronal loss. Method: Responses to the accumulation of plaques and tangles will involve all cell diversity in the brain. In particular, activation of glial cells such as microglia will start and promote neurodegeneration by eliminating debris from cells of protein aggregates around them. Model‐AD has collected cortex and hippocampus of 3xTgAD mice at different timepoints (4, 12, 18 and 24 months) to be characterized with RNA‐seq. We generated matching single‐cell and single‐nucleus from 12, 18 and 24‐month 3xTgAD mice using the ddSeq platform. The scRNA‐seq datasets were produced exclusively from isolated microglia. As an alternative to performing separate experiments for nuclei and cells, we have generated microglia + nuclei datasets from a 24‐month female 3xTgAD mouse using the SplitBio barcoding kit. Result: By analyzing out Bulk RNA‐seq data, we find three 3xTgAD modules that match AMP‐AD, 5xFAD modules significantly from comparing modules that we found by using WGCNA. One of these modules has AD neuroinflammation markers, while the other two have neuronal and oligodendrocyte markers. By analyzing scRNA‐seq data, we are able to detect distinct subpopulations of activated microglia enriched in the 3xTgAD mouse model using different microglia single‐cell and whole tissue singlenucleus techniques in cortex and hippocampus. Conclusion: We explore brain cell diversity as well as microglial sub populations in the 3xTgAD mouse models to generate additional insights about the cell response to AD.